Saving Grace - Green, Jane, 1968- (St. Martin's Press, 2015)
"Grace and Ted Chapman: literary power couple. Ted is considered 'the thinking man's John Grisham' and Grace, his wife of twenty years, is beautiful, stylish, carefree. All of this is on the surface; beneath, what no one sees, is Ted's rages. His mood swings. And the precarious house of cards that their lifestyle is built upon. When Ted's longtime assistant and mainstay leaves, the house of cards begins to crumble and Grace, with dark secrets in her past, is most vulnerable"--